Gender of the Consumer and Service Quality - Herath, H. M. R. P; Wanninayake, W. M. C. B (Journal of Commerce and Trade, 2009)
The banking sector in Sri Lanka grew rapidly in the recent years. Services sector accounts 56.2% of Gross Domestic Product in Sri Lankan economy which is the highest in all sectors where as the financial services which includes banking industry contribute 9.7% to total Gross Domestic Product. Further in Sri Lanka, financial system of the country mainly depends on banking system because banking sector represents a share of 70.8% of total financial system of the economy. Therefore identifying the significance of the gender of the consumers’ on the evaluation of service quality in the retail commercial banking industry of Sri Lanka is significantly important. Further, it is worth to identify whether there is any difference based on the gender of the consumers on evaluation of service quality of the banks that they are dealing with. Based on the stratified sampling technique 150 consumers were selected as the sample. The scope of the study was retail consumers of private and public commercial banks situated in the Gampaha district, who have been dealing with those particular banks more than two years. Survey method used to gather primary data and it was developed on SERVQUAL model of service quality. The gathered data were analyzed using ANOVA and findings showed that there is no any difference among the consumer groups based on their gender in terms of evaluation of service quality provided by the banks.